Higher CO2 Assimilation in Selected Rice Recombinant Inbred Lines Is Driven by Higher CO2 Diffusion and Light Use Efficiency Related to Leaf Anatomy and Mesophyll Cell Density - Zeng, Faliang; Zhu, Lin; Wang, Guojiao; Liang, Yinpei; Ma, Dianrong; Wang, Jiayu (Frontiers in Plant Science, 2022)
Leaf anatomy determining the light distribution within the leaf and exerting influence on CO2 diffusion is considered to have dramatic potential for photosynthesis performance increase. In this study, we observed two rice recombinant inbred lines, H138 and H217 (RILF11 plants from Sasanishiki×IRAT10), have higher net CO2 assimilation (An) than their parent Sasanishiki due mainly to the improvement of leaf anatomy. Our results showed that An positively correlated with anatomy traits mesophyll cell number per cross-sectional area (NO.mes cell/Acros) and mesophyll area (Ames). NO.mes cell/Acros exert direct and indirect effects on An. Compared to Sasanishiki flag leaves, IRAT10, H138, and H217 have higher mesophyll cell numbers. Simultaneously, higher chlorophyll content and expression of genes encoding the light-harvesting protein of PSII and PSI (Lhcb1, 2, 3 and Lhca1, 2, 3) were recorded in IRAT10, H138, and H217, which facilitates light use efficiency. Higher electron transport rate and RuBP concentration were recorded in IRAT10, H138 and H217 flag leaves. Retinoblastoma-related gene (OsRBR1) exerting effects on mesophyll cell density can be used to modify leaf anatomy for improving leaf photosynthesis. Additionally, higher stomatal conductance and mesophyll conductance were also recorded in H138 and H217 than in Sasanishiki. Furthermore, we modeled mesophyll conductance through anatomical traits, and the results revealed that chloroplast thickness was the dominant factor restricting CO2 diffusion within mesophyll cells rather than cell wall thickness. Higher RuBP content accompanied by higher CO2 concentration within the carboxylation set in H138 and H217 flag leaves contributed to higher CO2 assimilation.